1989
DOI: 10.1063/1.457601
|View full text |Cite
|
Sign up to set email alerts
|

Diffusivity of the hydrogen molecule sorbed in NaA zeolite by a neutron scattering experiment

Abstract: The diffusion of hydrogen in NaA zeolite was studied by incoherent neutron scattering. An experiment was carried out on samples loaded with 1.2 to 3.4 molecules per cavity and at several temperatures from 70 to 150 K. The angular (θ) dependence of the elastic and quasielastic intensities shows that the H2 molecule has a translational motion in a nonrestricted volume. A diffusion model where the molecule undergoes isotropic jumps of mean length l̄=3.9 Å independent of temperature and is at rest for a time τ0 be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
25
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 14 publications
6
25
0
2
Order By: Relevance
“…However, to date there have been no comprehensive studies of H 2 diffusivity and phase behavior in KC 24 . Previous studies of H 2 diffusion in zeolites and carbon nanostructures have reported thermally activated liquidlike diffusion, [20][21][22][23] but behavior in the ternary hydrogenpotassium-graphite intercalation compound may be more complicated. The combination of a two-dimensional geometry and a strong sorption potential could create interesting phases of the condensed hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…However, to date there have been no comprehensive studies of H 2 diffusivity and phase behavior in KC 24 . Previous studies of H 2 diffusion in zeolites and carbon nanostructures have reported thermally activated liquidlike diffusion, [20][21][22][23] but behavior in the ternary hydrogenpotassium-graphite intercalation compound may be more complicated. The combination of a two-dimensional geometry and a strong sorption potential could create interesting phases of the condensed hydrogen.…”
Section: Introductionmentioning
confidence: 99%
“…7 to values for single-walled carbon nanotubes, 45 zeolitetemplated carbon (ZTC), 48 and the conductive carbon black XC-72. 46 Also plotted are self-diffusion coefficients for the NaA zeolite, 43 the 13X zeolite, 44 and the metal-organic framework MIL-47. 49 An obvious feature in Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Variation of the Lorentzian HWHM versus Q is described by the isotropic jump diffusion model, which has been previously utilized to describe H 2 diffusion in zeolites and carbons. [43][44][45][46] This model assumes jumps of variable length in random directions, with a length distribution given by a(l) = l exp (−l/l 0 ). 29,47 Parameters obtained from this variable-jump-length isotropic diffusion model were similar to those obtained from the honeycomb net model, although their variation with temperature was smaller.…”
Section: Qens Measurementsmentioning
confidence: 99%
“…La DQEN a permis de mesurer la diffusion à longue distance dans la NaA [30] et la NaX [4] ; dans la chabazite [31] et la mordénite [32] seuls des mouvements locaux ont semble-t-il été observés. Des résultats récents viennent d'être obtenus par PFG NMR [33].…”
Section: Hydrogène Dans Les Zéolithes Naa Et Naxunclassified
“…I1 faut cependant tenir compte du fait que le rapport ortholpara H2 diminue avec la température, le para H2 diffusant beaucoup moins les neutrons de faible énergie. Avec H2 , les expériences ont été réalisées entre 70 et 150 K [30,4]. Pour pouvoir faire des mesures au-dessous de 20 K, on peut utiliser la molécule HD [34], étant donné que la séparation entre niveaux de rotation symétriques et antisymétriques n'existe plus.…”
Section: Hydrogène Dans Les Zéolithes Naa Et Naxunclassified